A Contrastive Study of Thai "Wai" and "Te-oku" Usage - Srikittiwanna, kitpakorn (Rajamangala University of Technology Tawan-ok Social Science Journal, 2025)
The objective of this qualitative research was to study the similarities and differences of using the word ’wai’ in the grammar ’te-oku’ in terms of meaning and use of grammatical functions. The researcher presented through the analytical reading accompanying the analysis table to thoroughly analyze and compare in terms of meaning and grammatical functions by doing descriptive writing accompanying the examples from the study of the differences in meaning and grammatical functions of the words and ’te-oku’ that comes after the verb. The researcher selected only 18 Thai songs for the scope of the study arranged in chronological order from 1992 to 2021, which were translated into Japanese based on the meaning and thematic of the lyrics. The results showed the words ’keep’, ’patient’, ’dig’, and ’bind’ are the words corresponding to the use of ’te-oku’ in Japanese which can only be used by the speaker. Also, it has the meaning of preparatory. Therefore, it was consistent with the meaning of ’te-oku’ in terms of preparation. In addition, the researcher found that Thai students who studies Japanese are still confused about the use of verbs co-occurring with the use of the grammar ’te-oku’. Because there were many verbs can be used with ’wai’ in Thai language such as ’mee wai’, ’dai wai’, ’luem wai’, ’khaw chai wai’ etc. In Japanese, these verbs are conditional. Moreover, it does not appear in the description in any textbooks causing the problem in the translation of the verbs co-occurring with ’te-oku’. Therefore, the researcher presents through this contrastive research to present the use of ’te-oku’ in the sentences correctly. Also, can be used to develop and improve the use of both Thai and Japanese language.